Caregivers' perceptions of the oral-health-related quality of life of children with special needs in Johannesburg, South Africa - Cathrine Nqcobo; Tshakane Ralephenya; Yolanda Kolisa; Temitope Esan; Veerasamy Yengopal (AOSIS, 2019)
Background: The prevalence of dental caries and its effect on the oral-health-related quality of life (OHRQoL) of children with special needs (CSNs) have not been established in South Africa. Aim: The study aimed to assess how caregivers of CSNs who attended Down Syndrome Association outreach sites in Johannesburg, South Africa, perceived the contribution of OHRQoL to the quality of life of these children. Setting: The study was conducted at Down Syndrome Association (DSA) outreach sites in Johannesburg. These sites cater for children with several types of disabilities including cerebral palsy, hydrocephalus, autism, epilepsy and developmental delays. The association schedules and facilitates support group meetings for the caregivers of children with Down syndrome and other disabilities. These meetings are held at the outreach sites that are located at different district hospitals and community health centres in Johannesburg and are co-facilitated by the association's outreach coordinator together with a team of physiotherapists, occupational therapists and speech therapists. Methods: This cross-sectional study was composed of a convenient sample of 150 caregiver and child pairs from five outreach sites during January - June 2015. The short-form Parent-Caregiver Perception Questionnaire (P-CPQ) was used. The caries status of the children was assessed using the decayed, missing and filled teeth (dmft/DMFT) indices (whereby dmft or DMFT stands for decayed missing filled teeth in primary dentition [dmft] and in permanent dentition [DMFT]) based on World Health Organization guidelines. Results: The mean age of the caregivers was 39.52 years (standard deviation [SD] 9.26) and 8.72 years (SD 6.07) for the children. The mean P-CPQ score was 12.88 (SD 12.14). All the caregivers stated that dental caries had a negative impact on the OHRQoL of the CSNs. However, 60% of caregivers stated that an oral condition had no impact on the child's overall well-being. The majority (56.7%) of the caregivers rated their children's overall oral health status as average and only 12% reported the oral health status to be poor. There was a high prevalence of untreated caries among the CSNs regardless of the type of disability. Conclusion: All the caregivers stated that dental caries had a negative impact on the OHRQoL of the CSNs. However, they appeared to have contradictory perceptions of the oral health needs or status of their children.